2006
DOI: 10.1002/ptr.1891
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and hepatotoxic effects of Ononis spinosa L.

Abstract: The present study investigated the analgesic and hepatoprotective activities of a water extract of Ononis spinosa L. (OS) in mice. Analgesic activity was based on the pain thresholds measured with the tail-flick test before administration at 30, 90 and 150 min. The results were analysed with one-way variance analysis. The extract of Ononis spinosa showed analgesic activity equivalent to aspirin at 30 and 90 min and even higher than aspirin with the 50 mg/kg dose. At a dose of 100 mg/kg OS showed an analgesic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
(4 reference statements)
0
11
0
2
Order By: Relevance
“…According to phytochemical studies on Ononis species, flavonoids, norpenyl propanoid glucosides, isocoumarins and hydroxycinnamic acids, triterpene, sterol, lectin, saponin, isoflavone, pterocarpane derivatives, resorsinol derivatives were isolated from several Ononis species (Blumental et al, 1998;Erdemgil et al, 2002;Yılmaz et al, 2006). In thin layer chromatography and qualitative analysis by using chemical reagents, we also found out that flavonoid type compounds are present in the ethanolic extract of the O. macrosperma aerial parts.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to phytochemical studies on Ononis species, flavonoids, norpenyl propanoid glucosides, isocoumarins and hydroxycinnamic acids, triterpene, sterol, lectin, saponin, isoflavone, pterocarpane derivatives, resorsinol derivatives were isolated from several Ononis species (Blumental et al, 1998;Erdemgil et al, 2002;Yılmaz et al, 2006). In thin layer chromatography and qualitative analysis by using chemical reagents, we also found out that flavonoid type compounds are present in the ethanolic extract of the O. macrosperma aerial parts.…”
Section: Resultsmentioning
confidence: 92%
“…In the previous studies, Ononis species have been shown to possess antimicrobial (Mahasneh and El-Oqlah, 1999;AbdelKader, 2001;Altanlar et al, 2006;Al-Bakri and Afifi, 2007), anti-inflammatory (Bremner et al, 2009(Bremner et al, ), antioxidant (Ç oban et al, 2003Tawaha et al, 2007), analgesic (Tulaikin and Bakhtina, 2006;Yılmaz et al, 2006), diuretic (Kassem et al, 1997;Tulaikin and Bakhtina, 2006), cytotoxic and antitumor effects (Leallau and Liebezeit, 2003).…”
Section: Resultsmentioning
confidence: 95%
“…Kelime tanõmadaki başlõca sorunlar; Òtanõnmayan kelimelerin okunmamasõ, sembol ile ses arasõndaki ilişkiyi kavrayamama, kelime veya harf karõştõrma, heceleme gŸçlŸğŸ, kelimedeki harflerin değiştirilmesi, tahmin ederek okuma, yanlõş okuma ve kelimeleri değiştirme, ekleme ve bõrakmalar, tersine çevirmeler, tekrarlamalarÓ biçiminde sõralanabilir (Uzunkol, 2013). Kelimeyi tanõma ve ayõrt etme yetisi gelişmemiş okuyucular, okuma sõrasõnda daha çok kelimeyi seslendirmekle meşgul olup anlamaya yeteri kadar zaman ayõramadõklarõ için okuma becerilerini geliştirmekte zorlandõklarõndan okuma esnasõnda çok sayõda hata yapmakta, akõcõ okuyamamakta ve okuduğunu anlayamamaktadõrlar (Yõlmaz, 2008;Dağ, 2010). Bu bireylerin akõcõ okumayõ šğrenmeleri için çeşitli stratejiler geliştirmek gerekmektedir.…”
Section: Okuma Beceri̇si̇ni̇n Geli̇şti̇ri̇lmesi̇nde Grafi̇ksel Sembolleri̇n Kuunclassified
“…spinosa exhibits antibacterial, antiviral, anti-inflammatory, cytotoxic, diuretic, purgative as well as analgesic activities (VOLLMER & HINDEMITU 1937;VOLLMER 1940a, b;HILV 1976;REBUELTA et al 1981;YILMAZ et al 2006). spinosa exhibits antibacterial, antiviral, anti-inflammatory, cytotoxic, diuretic, purgative as well as analgesic activities (VOLLMER & HINDEMITU 1937;VOLLMER 1940a, b;HILV 1976;REBUELTA et al 1981;YILMAZ et al 2006).…”
Section: Ononis Spinosa Lmentioning
confidence: 99%